3D‐printed individual labware in biosciences by rapid prototyping: In vitro biocompatibility and applications for eukaryotic cell cultures. Issue 1 (22nd August 2014) - Lücking, Tim H.; Sambale, Franziska; Schnaars, Birte; Bulnes‐Abundis, David; Beutel, Sascha; Scheper, Thomas
<x xml:space="preserve">Abstract</x> Three‐dimensional (3D) printing techniques are continuously evolving, thus their application fields are also growing very fast. The applications discussed here highlight the use of rapid prototyping in a dedicated biotechnology laboratory environment. The combination of improving prototypes using fused deposition modeling printers and producing useable parts with selective laser sintering printers enables a cost‐ and time‐efficient use of such techniques. Biocompatible materials for 3D printing are already available and the printed parts can directly be used in the laboratory. To demonstrate this, we tested 3D printing materials for their in vitro biocompatibility. To exemplify the versatility of the 3D printing process applied to a biotechnology laboratory, a normal well plate design was modified in silico to include different baffle geometries. This plate was subsequently 3D printed and used for cultivation. In the near future, this design and print possibility will revolutionize the industry. Advanced printers will be available for laboratories and can be used for creating individual labware or standard disposables on demand. These applications have the potential to change the way research is done and change the management of stock‐keeping, leading to more flexibility and promoting creativity of the scientists.